Analisis Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur - Sitti Nur Kholifah Aritmal; Indah Pratiwi; Riyanti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This financial performance study is vital for responsible a corporation's financial success. The goal the purpose of this research is to discover and investigate the effects of excellent corporate governance and firm scope on financial results. The dependent variable analyzed in this study is financial results, with the independent factors being the following proportion of board members, management equity, institutional investment, audit board, and firm size. This study relies on secondary data. The population includes 196 manufacturing firms. This study also incorporated data from 38 manufacturing businesses publicly listen the samples, taken from the Indonesia Standard Conversation (IDX). Were chosen through a purposive sample method strategy, yielding 114 samples during a three-year period spanning 2021 to 2023. This research employed manifold reversion examination, which was carried out according to the findings of this study, which were analyzed by the SPSS (Arithmetical Creation then Facility Answers) appeal. The proportions of commission board, management equity, and institutional investment significantly affect the company’s financial results. These companies' financial performance, however, is unaffected by the audit board or company size.